Comparison of bone and articular cartilage changes in osteoarthritis: a micro-computed tomography and histological study of surgically and chemically induced osteoarthritic rabbit models - Syed Sulaiman, Sharifah Zakiah; Tan, Wei Miao @ Rachel; Radzi, Rozanaliza; Shafie, Intan Nur Fatiha; Ajat, Mokrish; Mansor, Rozaihan; Mohamed, Suhaila; Min, Angela Hwei Ng; Lau, Seng Fong (BioMed Central, 2021)
Background: Osteoarthritis (OA) is a multifaceted condition that affects both the subchondral bones and the articular cartilage. Animal models are widely used as an effective supplement and simulation for human OA studies in investigating disease mechanisms and pathophysiology. This study is aimed to evaluate the temporal changes of bone and cartilage in surgically and chemically induced osteoarthritis using micro-computed tomography and histology. Methods: Thirty rabbits underwent either anterior cruciate ligament transection (ACLT) procedure or injected intraarticularly with monosodium iodoacetate (MIA, 8 mg) at the right knee joint. The subchondral bones were scanned via micro-CT, and articular cartilage was assessed histologically at 4-, 8- and 12-week post-induction. Results: Based on bone micro-architecture parameters, the surgically induced group revealed bone remodelling processes, indicated by increase bone volume, thickening of trabeculae, reduced trabecular separation and reduced porosity. On the other hand, the chemically induced group showed active bone resorption processes depicted by decrease bone volume, thinning of trabeculae, increased separation of trabecular and increased porosity consistently until week 12. Histologically, the chemically induced group showed more severe articular cartilage damage compared to the surgically induced group. Conclusions: It can be concluded that in the ACLT group, subchondral bone remodelling precedes articular cartilage damage and vice versa in the MIA group. The findings revealed distinct pathogenic pathways for both induction methods, providing insight into tailored therapeutic strategies, as well as disease progression and treatment outcomes monitoring.